Effect of acetylsalicylic acid intake on platelet derived microvesicles in healthy subjects. (17th February 2020) - Rosinska, Justyna; Maciejewska, Joanna; Narożny, Robert; Osztynowicz, Krystyna; Raczak, Beata; Michalak, Sławomir; Watała, Cezary; Kozubski, Wojciech; Łukasik, Maria
Abstract: Platelet-derived microvesicles (pMVs) are released from platelets in physiological and pathological conditions and exhibit a wide range of prothrombotic, antithrombotic, proatherogenic, and pro-inflammatory properties. Antiplatelet agents, such as acetylsalicylic acid (ASA), are widely used for the prevention and treatment of vascular diseases, but their impact on pMV release remains poorly understood and contradictory mainly because of discrepancies in the methodology and lack of well-standardized MV assessment protocols. The present study investigated the effects of ASA not only on total pMV release but also on their phenotypes defined using the surface expression of pro-inflammatory (CD40L, CD62P, CD31) and procoagulant (PS, PAC-1) markers in healthy subjects. Fifty healthy volunteers were enrolled in the study and received a daily dose of 150 mg ASA for 3 consecutive days. Circulating pMVs were characterized and quantified before and after the intervention period using flow cytometry. Serum levels of thromboxane B2 (TXB2) and whole blood impedance platelet aggregation under arachidonic acid (AA) stimulation were also investigated to assess ASA compliance. In general, ASA did not effect pMV numbers in healthy subjects despite its effective inhibition of platelet aggregation Moreover, in premenopausal women, we noticed an increase in the number of pMVs. Further studies are needed to assess whether dose modification of ASA or combinations or changes in antiplatelet therapy would reduce pMV formation, especially in patients with cardiovascular risk factors.